Causes and Consequences of Rising Food Prices - Georg Erber; Martin Petrick; Vanessa von Schlippenbach (Weekly Report, 2008)
Since mid 2007 there has been a dramatic rise in prices for basic foods such as internationally traded varieties of rice, corn and wheat. At the moment, it is rather impossible to estimate how far speculation in the commodity markets has contributed to this development. Irrespective of this, a long-term solution to present and future supply shortfalls, including investment in more efficient agro-technologies and infrastructures is required. This is a matter for the international community which should continue to promote the abolition of international trade barriers in the agricultural sector in addition to local measures to provide structural aid. Hoped-for structural change may however be impeded if agricultural producers are exposed both to the market power of trader demand and the supplier power of upstream suppliers. It therefore appears that controls on abuse of market power at an international level are urgently required in order to increase the efficiency of agricultural markets and ultimately to secure the food supply.
Keywords: D84; L4; Q11; Q17; 330; Noisetraders; Trade liberalization; Vertical relations